The effect of annealing and the influence of Gamma-ray on the optical properties of nanostructure Zinc Oxide Thin Films - Saeed, Nada M. (Iraqi Journal of Physics, 2010)
The semiconductor ZnO is one of II – VI compound group, it is prepare as thin films by using chemical spray pyrolysis technique; the films are deposited onto glass substrate at 450 °C by using aqueous zinc chloride as a spray solution of molar concentration 0.1 M/L. Sample of the prepared film is irradiating by Gamma ray using CS 137, other sample is annealed at 550°C. The structure of the irradiated and annealed films are analyzed with X-ray diffraction, the results show that the films are polycrystalline in nature with preferred (002) orientation. The general morphology of ZnO films are imaged by using the Atomic Force Microscope (AFM), it constructed from nanostructure with dimensions in order of 77 nm.The optical properties of the prepared films are studied by using measurement from UV-VIS-NIR spectrophotometer at wavelength within the range (300-900) nm. The optical results show that the absorption of the prepared films are decreases after annealing and increases after irradiation. The optical constants such as the refractive index and the photoconductivity are calculated before and after annealing as a function of the photon energy. Also the values of the optical energy gap are calculated, it is 3.3 eV and 3.1 eV for the direct and indirect allowed transition respectively; these values are reduced after annealing.